Mengahadapi Kapitalisme dalam Konteks Hukum Indonesia - firmansyah, firmansyah; firmasyah, firmansyah (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2022)
The grip of capitalization has been so widespread that it has even gripped the ideological aspect of a country so that it becomes a problem in the preparation of positive law in the Indonesian context. The purpose of this study was to determine the impact of capitalization and efforts to counteract the effect of capitalization in a positive legal perspective. The approach taken is normative with library research techniques. The results of the study stated that to deal with capitalization in the legal context in Indonesia using the theory of L.W. Friedaman with improvements in 3 (three) aspects, namely substance, structure and culture in an integrated manner.